S100a9 Protects Male Lupus-Prone NZBWF1 Mice From Disease Development - Davison, Laura M.; Alberto, Andres A.; Dand, Hardik A.; Keller, Emma J.; Patt, Madeline; Khan, Ayesha; Dvorina, Nina; White, Alexandra; Sakurai, Nodoka; Liegl, Lauren N.; Vogl, Thomas; Jorgensen, Trine N. (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disorder disproportionally affecting women. A similar sex difference exist in the murine New Zealand Black/White hybrid model (NZBWF1) of SLE with all females, but only 30-40% of males, developing disease within the first year of life. Myeloid-derived suppressor cells (MDSCs) are prominent in NZBWF1 males and while depletion of these cells in males, but not females, promote disease development, the mechanism of suppression remains unknown. S100a9, expressed by neutrophils and MDSCs, has previously been shown to exert immunosuppressive functions in cancer and inflammation. Here we investigated if S100a9 exert immunosuppressive functions in NZBWF1 male and female mice. S100a9+/+, S100a9+/- and S100a9-/- NZBWF1 mice were followed for disease development for up to 8 months of age. Serum autoantibody levels, splenomegaly, lymphocyte activation, glomerulonephritis and proteinuria were measured longitudinally or at the time of harvest. In accordance with an immunosuppressive function of MDSCs in male mice, S100a9-deficient male NZBWF1 mice developed accelerated autoimmunity as indicated by increased numbers of differentiated effector B and T cells, elevated serum autoantibody levels, increased immune-complex deposition and renal inflammation, and accelerated development of proteinuria. In contrast, female mice showed either no response to S100a9-deficiency or even a slight reduction in disease symptoms. Furthermore, male, but not female, S100a9-/- NZBWF1 mice displayed an elevated type I interferon-induced gene signature, suggesting that S100a9 may dampen a pathogenic type I interferon signal in male mice. Taken together, S100a9 exerts an immunosuppressive function in male NZBWF1 mice effectively moderating lupus-like disease development via inhibition of type I interferon production, lymphocyte activation, autoantibody production and the development of renal disease.